Kawasaki disease following SARS-CoV-2 infection: Stronger inflammation with no increase in cardiac complications - Roh, Da Eun; Lim, Young Tae; Kwon, Jung Eun; Kim, Yeo Hyang (Frontiers in Pediatrics, 2022)
Background: Herein we investigate the difference between Kawasaki disease (KD) with and without a recent history of SARS-CoV-2 infection. Methods: We compared the clinical characteristics of patients with KD during the SARS-CoV-2 pandemic in a single children’s hospital in Korea. Fifty-two patients were enrolled and divided into group 1 (with a history of COVID-19, n=26) and group 2 (without a history of COVID-19, n=26) according to whether or not they contracted COVID-19 within the 8 weeks before hospitalization. Data, including clinical features and laboratory results, were analyzed and compared between groups. Results: The median age of patients was significantly higher in group 1 than in group 2 (53 months (IQR 24-81) vs. 15 months (IQR 6-33), p=0.001). The incidence of cervical lymphadenopathy was significantly higher (p=0.017), while that of BCGitis was significantly lower in group 1 (p=0.023), and patients had a significantly longer hospital stay (5(IQR 3-8) days vs. 3(IQR 3-4) days), p=0.008). In group 1, platelet count was significantly lower (p=0.006), and hemoglobin and ferritin levels were significantly higher (p=0.013 and p=0.001, respectively) on the first admission day. Only one patient in Group 1 developed the multisystem inflammatory disease (MIS-C). Following treatment with intravenous immunoglobulin, the platelet count was significantly lower (p=0.015), and the percentage of neutrophils and neutrophil-to-lymphocyte ratio were significantly higher in group 1 (p=0.037 and p=0.012). The incidence of cardiovascular complications did not differ between the groups. Conclusions: Post-COVID KD showed a stronger inflammatory response than KD-alone, with no differences in cardiac complications or IVIG resistance.